2022
DOI: 10.3389/fcvm.2022.862999
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lipid Levels With COVID-19 Infection, Disease Severity and Mortality: A Systematic Review and Meta-Analysis

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) ranges from asymptomatic infection to severe illness. Cholesterol in the host cell plasma membrane plays an important role in the SARS-CoV-2 virus entry into cells. Serum lipids, especially low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C), are in constant interaction with the lipid rafts in the host cell membranes and can modify the interaction of virus with host cells and the resultant disease severity. Recent studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 53 publications
(65 reference statements)
2
13
0
1
Order By: Relevance
“…On the contrary, recent evidence suggests that low serum levels of LDL-C, HDL-C, and total cholesterol (TC) at hospital admission are associated with severe disease and mortality in COVID-19. 7,8 However, these associations were based on measurements made during hospital admission and suffer from the possibility of reverse causality due to the acute inflammatory response in COVID-19. Additionally, clinical data on the impact of past HDL-C and LDL-C levels on the risk and outcome of infectious diseases remain inconsistent.…”
Section: Research In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, recent evidence suggests that low serum levels of LDL-C, HDL-C, and total cholesterol (TC) at hospital admission are associated with severe disease and mortality in COVID-19. 7,8 However, these associations were based on measurements made during hospital admission and suffer from the possibility of reverse causality due to the acute inflammatory response in COVID-19. Additionally, clinical data on the impact of past HDL-C and LDL-C levels on the risk and outcome of infectious diseases remain inconsistent.…”
Section: Research In Contextmentioning
confidence: 99%
“…5,6 On the contrary, recent evidence suggests that low serum levels of LDL-C, HDL-C, and total cholesterol (TC) at hospital admission are associated with severe disease and mortality in COVID-19. 7,8 However, these associations were based on measurements made during hospital admission and suffer from the possibility of reverse causality due to the acute inflammatory response in COVID-19. 9 Among the various serum lipoprotein fractions, preclinical evidence suggests that HDL-C is an important modulator of inflammation, 10,11 with potential mechanisms including interference with viral fusion, reduction in the rate of bacterial complications, and neutralization of exaggerated immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Further work is needed to establish the mechanisms driving SPC and whether they are reflective of treatable traits. Animal and human studies, for example, already highlight lipoproteins as potential therapeutic targets in sepsis (Tanaka et al, 2020) and COVID-19 (Chidambaram et al, 2022). Additional work is also required to determine the maximally informative biomarkers appropriate for point of care testing, and whether these can be applied in combination with other 'omic platforms and currently available clinical or laboratory variables to better stratify patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have reported that patients with diverse infections, such as Epstein–Barr virus, cytomegalovirus and tuberculosis, had lower levels of lipoproteins in comparison with non-infected individuals. 1–3 In the research by Vignesh et al , 4 lower lipid was also observed in COVID-19 patients compared to uninfected controls. Consistent with these reports, our research revealed the reduced lipoprotein pattern in Omi-Rec patients and highlights the important role of lipid metabolism in SARS-CoV-2 shedding.…”
mentioning
confidence: 87%